Motivations For Visiting And Not Visiting Museums Among Young Adults: A Case Study On Uum Students - Mokhtar, Muhammad Fauzi; Kasim, Azilah (Global Research Agency, 2012)
Marketing management is an important managerial dimension that must be continually assessed to ensure profit. It includes understanding target markets that could provide desired return to the organization, but are difficult to access. In the contexts of museums in Malaysia, this potentially lucrative but reluctant market is the youth market. This study looks at 1. The motivations of young adults for visiting museums, 2. The reasons inhibiting them from visiting museums, and 3. Their perceptions on how museums should be marketed to attract young adults. Using a questionnaire survey, 1036 usable questionnaires were analyzed to fulfill the research objectives. The findings indicate that youth within the study context has higher predisposition to visit museums and could be a potential sub segment to target when marketing museums to young adults. In addition, a majority of them has an overall positive image of museums, thereby contrasting the theory that young adults tend to see museums as boring, didactic and unapproachable. However, the motivations of visit found in this study shows that practicality can motivate young adults to visit museum. Among respondents who have never visited museums in the last three years, the main reason for not visiting was the lack of time, followed by lack of interest in museum, and lack of information about the museum offerings. Other reasons for not visiting museum include the preference for other activities, difficulties in getting required information about museums and the tendency to put off visiting until a later date and the perception that museum admission fees are too pricy. A very small percentage of the respondents simply indicated that they do not like to visit museum. Brochures, strong web presence and guides in the museums are promotional tools that youth would like to see. Lower admission fees. More attractive museum collections and displays and updated website information are additional measures museum marketers can take in trying to reach and specifically target this young adult’s market segment